Children's erythrocyte fatty acids are associated with the risk of islet autoimmunity - Niinistö Sari; Erlund Iris; Lee Hye-Seung; Uusitalo Ulla; Salminen Irma; Aronsson Carin Andén; Parikh Hemang M; Liu Xiang; Hummel Sandra; Toppari Jorma; She Jin-Xiong; Lernmark Åke; et al. (NATURE RESEARCH, 2025)
Our aim was to investigate the associations between erythrocyte fatty acids and the risk of islet autoimmunity in children. The Environmental Determinants of Diabetes in theYoung Study (TEDDY) is a longitudinal cohort study of children at high genetic risk for type 1 diabetes (n = 8676) born between 2004 and 2010 in the U.S., Finland, Sweden, and Germany. A nested case-control design comprised 398 cases with islet autoimmunity and 1178 sero-negative controls matched for clinical site, family history, and gender. Fatty acids composition was measured in erythrocytes collected at the age of 3, 6, and 12 months and then annually up to 6 years of age. Conditional logistic regression models were adjusted for HLA risk genotype, ancestry, and weight z-score. Higher eicosapentaenoic and docosapentaenoic acid (n - 3 polyunsaturated fatty acids) levels during infancy and conjugated linoleic acid after infancy were associated with a lower risk of islet autoimmunity. Furthermore, higher levels of some even-chain saturated (SFA) and monounsaturated fatty acids (MUFA) were associated with increased risk. Fatty acid status in early life may signal the risk for islet autoimmunity, especially n -3 fatty acids may be protective, while increased levels of some SFAs and MUFAs may precede islet autoimmunity.